Consumer education in secondary schools in Botswana: perceptions of home economics teachers - Peters, Selinah, author; Makela, Carole J., advisor; Albright, Leonard, committee member; Wallner, Barbara K., committee member; Drennen, Nancy, committee member (Colorado State University. Libraries, 2007)
Consumer education is interdisciplinary and empowers students with decision making skills and enhances their roles as competent consumers, producers, and citizens. It empowers students to be effective managers of resources and to improve their wellbeing as individuals and families. The purpose of this study was to assess the perceived needs and explore the quality of the consumer education modules taught in senior secondary schools in Botswana. Participants were home economics senior secondary school teachers from 20 schools. The schools were randomly sampled from a list of all 27 senior secondary schools in the country. The list was obtained from the Ministry of Education in Botswana. To answer the research questions, a questionnaire was developed with ideas adopted from other studies and consultation with home economics teachers and stakeholders. The questionnaire had seven content areas–issues in consumer education modules, methods and experiences used to teach consumer education, availability of resources for teaching consumer education, content of consumer education modules, students' learning activities and performance, professional development/teacher learning, and teachers' demographic profile. In addition, an observation worksheet was used to assess the classroom learning environment for consumer education. Questionnaires were administered in person by the researcher to 101 home economics teachers. Eighty-seven questionnaires were returned and 86 (85.0%) were usable. Data was analyzed using descriptive and inferential statistics. The findings revealed that a majority (99.0%) of the home economics/consumer education teachers were females and more than two-thirds taught in rural schools. The highest degree attained by most teachers was Bachelor of Science/Bachelor of Arts. A substantial percentage (85.7%) of the teachers majored in home economics and a small percentage (12.0%) majored in consumer education/sciences. Fifty-nine percent perceived their backgrounds as moderate for teaching consumer education. In relation to teaching and learning resources, there were no prescribed textbooks and aids such as teachers' instructional guides and video tapes on consumer education in almost all the schools including in their libraries. Almost all schools had computer labs and each home economics department had one computer for teachers' use but there were no internet connections. Computer use was restricted to students who were enrolled in computer awareness classes. Among others, teachers expressed the need for prescribed textbook(s) with up-to-date, relevant, adequate information, related to Botswana. There were no significant differences in the availability of teaching resources between rural and urban schools. The quality of consumer education as perceived by teachers was good in meeting goals and objectives and essentiality of objectives to students' learning. Teachers were uncertain about the comprehensiveness of content to prepare students for work and family life. All the teachers perceived themselves as competent to teach each of the objectives/topics of the modules and most said they had problems on deciding the depth or amount of the consumer education objectives/topics to teach. There were no significant relationships of teachers' level of competency in teaching each of the objectives and their levels of education. Three common methods (group discussion, chalk board, and lecture) were used by more than 50.0% of the teachers to teach each of the consumer education objectives/topics and most common student experiences were students' presentations and research. Teachers perceived their strengths as being knowledgeable in teaching consumer education and their background/training in consumer education. Their weaknesses were the opposite of their perceived strengths. Teachers indicated that students were as interested in consumer education as they were in other topics taught and were able to apply what they learned. The majority of teachers were not active in professional development activities despite the fact that they knew that participation in such activities could enhance their consumer knowledge and skills. Recommendations to improve the quality of consumer education in secondary schools in Botswana were made. They included provision of teaching and learning resources to schools, for example, textbooks, teaching aids, and the internet. Others were moral and financial support for teachers' participation in professional development activities and collaboration initiatives, and that consumer education should be taught as a core subject at secondary schools and at Botswana colleges of education.
Keywords: home economics education; secondary education; curricula; teaching; curriculum development